Learning techniques and keeping in mind what is learned during reading - Gaxhiqi, Behxhet (Technium Social Sciences Journal, 2022)
The aspect of learning and memory is developed on the basis of the development of learning abilities and its cognitive elements. Within this paper we will reflect the factors, but also the techniques that directly affect the learning process. In the framework of this paper I will analyze, justify, the factors but also the strategies that influence the process of learning. As is well known, human intelligence facilitates the process of learning and memory, while learning enables the development of intelligence, which in many definitions and scientific arguments determines the ability of learning. Within this paper is also analyzed the relationship and the relationship between intelligence and memory, as well as the other theme of this work is the interconnection between what is taught and clearly understood during the reading and learning process. Also within this paper we have analyzed the cognitive style and other aspects related to memory. As is known, the cognitive style mainly has no conscious dimension, and the learning and memory strategy has to do with deciding how to learn and remember more. Also within this work is the role and building of human personality as it is a factor that is directly related to learning and keeping in mind what is taught.